INOVASI PEMBUATAN KERIPIK CENTELLA ASIATICA (RENDENG) DAN STRATEGI PEMASARAN DIGITAL DI DESA LARANGANLOR - Rafly Fadel Muhammad; Millati Himayatuna; Syifa Nurul Afidati; Isti Farihah; Supriyadi Supriyadi; Siti Khoiriyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Centella asiatica (locally “rendeng”) is often considered a weed despite its nutritional and economic potential. This community-engaged study aimed to develop an innovative Rendeng chip product and evaluate a digital marketing strategy to empower residents of Laranganlor Village. The method was a qualitative community service approach consisting of stakeholder confirmation, community socialization, hands-on product training, packaging instruction, and guided digital marketing (WhatsApp Business, e-commerce, simple visual content). Key findings: local government support facilitated implementation; technical training and improved packaging raised product quality; digital marketing expanded market reach and produced initial sales inquiries; monitoring revealed gaps in recipe standardization, equipment (precision scales, oil thermometers), and digital literacy that must be addressed to ensure sustainability and scale-up.